Ocular penetration of topically applied 1% tigecycline in a rabbit model - Sakarya, Yasar (Int J Ophthalmol, 2017)
AIM: To evaluate ocular penetration of topically applied 1% tigecycline. METHODS: Forty-two New Zealand White rabbits were divided into 3 groups. A 50 µL drop of 1% tigecycline was administered in group 1. In groups 2 and 3, the drop was administered every 15min for 60min (keratitis protocol). Aqueous humor samples in groups 1 and 2 were collected under general anesthesia at 15, 30, 45, 60, 120, and 180min after the last drop. All animals in group 3 were euthanatized. Cornea, vitreous and blood samples were collected 60 and 120min after the last drop. Tigecycline concentrations were measured using high performance liquid chromatography-mass spectrometry (LC-MS/MS). RESULTS: The peak aqueous humor tigecycline concentration [mean 0.73±0.14 mg/L (SD) and 2.41±0.14 mg/L, respectively] occurred 45min after topical drug application in groups 1 and 2. Group 3 mean values in the cornea, and vitreous, were 3.27±0.50 µg/g, and 0.17±0.10 mg/L at 60min and 3.17±0.77 µg/g and 0.20±0.07 mg/L at 120min, respectively. Tigecycline serum concentrations were negligible. CONCLUSION: Tigecycline levels in the aqueous humor in groups 1 and 2, and in the cornea in group 3 exceeded the minimum inhibitory concentrations of most gram-positive organisms that cause bacterial keratitis and endophthalmitis.